how do i solve

(e^x + e^-x)/ (e^x - e^-x)

ln(log(x)) = 0

sqrt(ln x) = ln sqrt(x)

(log3X)^2 - log3X^2 = 3

ln x^2 = (lnx)^2

5^(2x) - 3(5^x) +2 = 0

ln x ^(lnx) = 4

Printable View

- Dec 13th 2009, 01:34 PMcheezeandbunniesExponential and Logarithmic Equations
how do i solve

(e^x + e^-x)/ (e^x - e^-x)

ln(log(x)) = 0

sqrt(ln x) = ln sqrt(x)

(log3X)^2 - log3X^2 = 3

ln x^2 = (lnx)^2

5^(2x) - 3(5^x) +2 = 0

ln x ^(lnx) = 4 - Dec 13th 2009, 11:17 PMbigwave(e^x + e^-x)/ (e^x - e^-x)

this one is just an expression did you mean to set to zero

otherwise all one can is just come up with an alternate form - Dec 13th 2009, 11:51 PMred_dog
1)

The equation can be written as

Square both members:

Now continue.

2)

Let and solve the quadratic.

3)

4)

Let and solve the quadratic.

5) - Dec 14th 2009, 05:41 AMSoroban
Hello, cheezeandbunnies!

Here's some help . . .

Quote:

. . . . not an equation

Quote:

We have: .

Therefore: .

Quote:

We have: .

Square both sides: .

Factor: .

Therefore: .

Quote:

We have: .

Factor: .

Therefore: .